2013
DOI: 10.1177/0023677212473715
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring chronic physical stress using biomarkers, performance protocols and mathematical functions to identify physiological adaptations in rats

Abstract: This study was undertaken to characterize the effects of monotonous training at lactate minimum (LM) intensity on aerobic and anaerobic performances; glycogen concentrations in the soleus muscle, the gastrocnemius muscle and the liver; and creatine kinase (CK), free fatty acids and glucose concentrations in rats. The rats were separated into trained (n ¼ 10), baseline (n ¼ 10) and sedentary (n ¼ 10) groups. The trained group was submitted to the following: 60 min/day, 6 day/week and intensity equivalent to LM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…HIIT has been an important protocol of signaling to a multitude of target cells allowing aerobic adaptations during short term further than traditional endurance training (de Araujo et al, 2013a). Some studies reported that endurance training in rats may attenuate the natural loss, but not increase the aerobic capacity in comparison to baseline (de Araujo et al, 2012, 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…HIIT has been an important protocol of signaling to a multitude of target cells allowing aerobic adaptations during short term further than traditional endurance training (de Araujo et al, 2013a). Some studies reported that endurance training in rats may attenuate the natural loss, but not increase the aerobic capacity in comparison to baseline (de Araujo et al, 2012, 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…de Araujo et al (2013b) reported that monotonous training in swimming rats at intensity correspondent to 100 % of AT, decreased the training volume and increased serum CK concentration; suggesting that exercise at constant intensity cannot be applied in longterm training to improve the aerobic performance. Although these authors found glycogen supercompensation, the stores were not mobilized to increase the aerobic performance and to sustain the estimated volume.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the Wistar rats, the LMT is extensively used in different contexts as a valuable tool to estimate the aerobic capacity. In addition, authors have used the time to exhaustion (i.e., T lim), obtained during the second swim effort at 13% of the body mass (phase 1; de Araujo et al, 2007), as an anaerobic metabolism indicator (de Araujo et al, 2012, 2013a,b). Thus, the LMT is considered a complete evaluation for Wistar rats, forasmuch as in one aerobic and anaerobic test results can be achieved.…”
Section: Animal Models and The Lmtmentioning
confidence: 99%